A 24 GHz Wireless Sensor Network with High Precision Local Positioning Capability - Ferizi, Alban; Jung, Melanie; Weigel, Robert (IMS 2011 Workshop: Smart Wireless Sensor Networks (MTT-S), 2011)
elib2cris::1512001600,ferizi2011

A 9.7 mW 0.13 um CMOS PLL for Use in 24 GHz Sensor Nodes - Jung, Melanie; Ferizi, Alban; Ußmüller, Thomas; Fischer, Georg; Weigel, Robert (IEEE International Midwest Symposium on Circuits and Systems, 2011)
elib2cris::1512001600,jung2011a

A Chargepump with enhanced Current Matching and reduced Clock-Feedthrough in Wireless Sensor Nodes - Jung, Melanie; Ferizi, Alban; Weigel, Robert (Asia Pacific Microwave Conference, 2010)
Today, most of the locating systems are based on phase-locked loop (PLL) architectures for synthesizers. The synthesizer as a key element for location accuracy needs a chargepump with an exact current matching for improved phase noise performance. Especially in indoor scenarios, where sensor nodes must reach a precision below a few centimeters, the fidelity of the synthesizer system is important. This paper addresses the design of a chargepump with enhanced current matching and reduced clock-feedthrough in a FMCW based sensor node. The difference between a conventional chargepump design and the enhanced design is presented and compared to show the current matching improvement and clock-feedthrough reduction. The different designs were manufactured in a 0.13μm CMOS process by IBM. They are running in a PLL with 128MHz reference frequency and have an output current of 100μA with a total power consumption of 1mW for the chargepump with phase-frequency detector (PFD).
elib2cris::1512001600,jung2010a
Keywords: Clocks; Phase frequency detector; Phase locked loops; Transconductance; Transistors; Wireless communication; Wireless sensor networks

A Chip-Area-Efficient Baseband Processing Core for FMCW Radar-based Sensor Network Localization - Ferizi, Alban (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

A customizable UHF RFID-Reader for RFID-S Testing Applications - Hofmann, Andreas; Brenk, Daniel; Boehme, Andreas; Cilek, Fatih; Ferizi, Alban; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2011)
This paper describes a custom-built UHF RFID-Reader-Device with functionality to send and receive EPCglobal custom commands. It can be used to access enhanced capabilities in transponders, for example readout of integrated sensors. The device was implemented using a Xilinx FPGA and is fully controllable from a PC through a customizable MATLAB-Interface. This enables a step by step test of newly developed tags. All mandatory EPCglobal commands are implemented as well as EPC custom command capability.
elib2cris::1512001600,hofmann2011
Keywords: Graphical user interfaces; Protocols; Radiation detectors; Radiofrequency identification; Software; Transceivers

A digital trimmable comparator for high precision ADCs in wireless sensor nodes - Jung, Melanie; Ferizi, Alban; Ußmüller, Thomas; Fischer, Georg; Weigel, Robert (Semiconductor Conference Dresden, 2011)
elib2cris::1512001600,jung2011b

An Active Constraint Method for Distributed Routing, and Power Control in Wireless Networks - Ferizi, Alban; Dekorsy, Armin; Fliege, Jörg; Popova, Larissa; Koch, Wolfgang; Söllner, Michael (EURASIP Journal on Wireless Communications and Networking, 2009)
Efficiently transmitting data in wireless networks requires joint optimization of routing, scheduling, and power control. As opposed to the universal dual decomposition we present a method that solves this optimization problem by fully exploiting our knowledge of active constraints. The method still maintains main requirements such as optimality, distributed implementation, multiple path routing and per-hop error performance. To reduce the complexity of the whole problem, we separate scheduling from routing and power control, including it instead in the constraint set of the joint optimization problem. Apart from the mathematical framework we introduce a routing and power control decomposition algorithm that uses the active constraint method, and we give further details on its distributed application. For verification, we apply the distributed RPCD algorithm to examples of wireless mesh backhaul networks with fixed nodes. Impressive convergence results indicate that the distributed RPCD algorithm calculates the optimum solution in one decomposition step only.
elib2cris::1512001600,ferizi2009

An area-efficient 130 nm CMOS baseband processing unit for 24 GHz FMCW radar positioning - Ferizi, Alban; Baust, Philipp; Jung, Melanie; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (International Symposium on Signals, Systems, and Electronics (ISSSE), 2012)
This paper presents an area-efficient digital implementation of a baseband processing unit (BPU) for autonomous wireless sensor nodes with localization functionality. The presented wireless nodes should achieve a high miniaturization degree and use an onboard FMCW secondary radar for distance measurements. The challenge for designing the digital system was to reduce memory requirements towards a low cost hardware design in general, and for an ASIC design in particular. Reducing chip area implies lower energy consumption and helps saving implementation and production costs. At the same time a qualitative performance of the digital signal processing tasks while keeping the system constraints has to be assured. The introduced novel hardware implementation concept fulfill these criteria, and has been implemented and verified on a FPGA before starting the chip design. For the use case of a two-sweep-measurement-system the design has been realized as an ASIC using IBM 130nm CMOS technology.
elib2cris::1512001600,ferizi2012b
Keywords: Application specific integrated circuits; Baseband; Hardware; Radar; Random access memory; Wireless communication; Wireless sensor networks

Baseband Signal Processing for Wireless Sensor Nodes with Capability of FMCW Local Positioning - Ferizi, Alban; Kölpin, Alexander (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2012)
elib2cris::1512001600,ferizi2012a

CMOS Signalverarbeitung im Basisband für Sensornetzwerke mit Lokalisierungsfunktion - Jung, Melanie; Ferizi, Alban; Weigel, Robert (RADCOM, 2010)
elib2cris::1512001600,jung2010

Design and Implementation of a Fixed-Point Radix-4 FFT Optimized for Local Positioning in Wireless Sensor Networks - Ferizi, Alban; Höher, Bernhard; Jung, Melanie; Fischer, Georg; Kölpin, Alexander (9th International Multi-Conference on Systems, Signals & Devices, 2012)
elib2cris::1512001600,ferizi2012

Design of a 12 ghz low-power extended true single phase clock (e-tspc) prescaler in 0.13 um cmos technology - Jung, Melanie; Fuhrmann, Jörg; Ferizi, Alban; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (Asia-Pacific Microwave Conference, 2011)
elib2cris::1512001600,jung2011d

Distributed Routing and Power Control Algorithms in Fixed Wireless Networks - Ferizi, Alban (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)

High Precision Local Positioning for Wireless Industry Automation - Zohny, Amr; Ferizi, Alban; Rose, Richard; Weigel, Robert (Embedded World Conference 2011, 2011)
Wireless local positioning systems (WLPS) are currently becoming more entrenched in several elds. Among their most prominent elds of implementations are smart factories and real-time based active mapping for cultural guiding purposes. The development of such systems began with the realization of the positioning core technology. However, as this technology matured, more abstract system aspects materialized as the forthcoming challenge such as infrastructure demands in terms of ranging capabilities, cell requirements regarding bandwidth and most importantly, the energy obligations of the mobile unit. A popular solution to these system demands presents itself as the frequency modulated continuous wave (FMCW) radar technique. The aim of this paper is to discuss its underlying principle, the latest and most recent improvements in this system architecture
elib2cris::1512001600,zohny2011
Keywords: radar; local positioning; radio position measurement; industry automation

Lokalisierung in Sensornetzwerken und deren Basisbandverarbeitung - Jung, Melanie; Ferizi, Alban; Weigel, Robert (HF-Praxis, 2011)
Die Vielfalt der Lokalisierung- und Ortungssysteme stieg in den vergangenen Jahren rasant an. Neben den bekannten Ortungsverfahren über Galileo und GPS im privaten und industriellen Einsatz gewinnt die Lokalisierung innerhalb von Gebäuden immer mehr an Bedeutung. Hierbei sind besonders die meist auf FMCW (Frequency Modulated Continuous Wave) basierenden Sensornetzwerke hervorzuheben, die eine Vielzahl an Einsatzmöglichkeiten erlauben. Die Verbesserung von Produktionsabläufen durch Positionsbestimmung von Waren, Produktionsmitteln oder Maschinen ist ein mögliches Einsatzgebiet, aber auch die verbesserte Orientierung von Feuerwehr oder anderen Einsatzkräften in Gebäuden ist denkbar. Im Gegensatz zu satellitengestützten Ortungssystemen entstehen bei lokalen Systemen innerhalb von Gebäuden mehr Reflektionen des Signals an Oberflächen. Um die damit verbundene Mehrwegeausbreitung bestmöglich zu handhaben, bestehen hohe Anforderungen an das System und die Signalverarbeitung im Basisband. In diesem Beitrag wird die CMOS Signalverarbeitung im Basisband für einen Sensorknoten mit Lokalisierung näher beleuchtet. Diese wird im Gegensatz zu anderen Ansätzen vollständig in CMOS auf einem Chip realisiert, um so Platz- und Energiebedarf zu reduzieren. Auf diese Weise werden die Massenfabrikation und der großflächige Einsatz erleichtert.
elib2cris::1512001600,jung2011

Simulation Model for Performance Analysis of UMTS-Networks with Variable Data Rate - Ferizi, Alban (2006)